Gender Perspectives in Education: Strengthening Gender-Responsive Values to Achieve Sustainable Development Goals in the Globalization Era - Banu Ramanan; Mua'zam Mohamad (Journal of Gender and Millennium Development Studies, 2025)
Background: This study was motivated by the continued presence of gender bias in education in the era of globalization, where equality is often misunderstood as merely giving the same treatment to all students rather than addressing their diverse learning needs. Such misconceptions reinforce subtle forms of discrimination and limit students’ opportunities for equitable participation. Objective: This study aims to examine how gender-sensitive education strengthens students’ gender responsiveness and how these efforts align with the Millennium Development Goals (MDGs/SDGs), particularly those promoting gender equality and quality education. Method: A qualitative approach was employed using Fairclough’s Critical Discourse Analysis model. Data were collected through document analysis and interviews with teachers, counselors, and students to capture both textual and experiential dimensions. Results: The findings reveal that educational texts and practices continue to reproduce gender-role stereotypes and masculine leadership norms, although gradual improvements are evident through revised teaching materials, more inclusive classroom strategies, and increasing student agency. Conclusion: Gender-responsive education becomes effective when systematically embedded within the curriculum, guidance and counseling services, and school governance, and when aligned with SDG 4.7 and SDG 5 indicators. Contribution: This study provides theoretical, methodological, and practical insights that advance efforts to promote gender-equitable education in support of sustainable development.